The Evolution of Homeownership Rates in Selected OECD Countries: Demographic and Public Policy Influences - Andrews, Dan (OECD Publishing, 2011)
Homeownership rates have increased significantly in many OECD countries over recent decades. Using micro-econometric decomposition techniques, this paper shows that part of this increase can be explained by changes in the characteristics of households, including age, household structure, income and education. Nevertheless, a significant portion of the change in homeownership rates remains unexplained by shifts in household characteristics, leaving a potential role for public policy in explaining developments in homeownership rates. Panel estimates suggest that the relaxation of down-payment constraints on mortgage loans has increased homeownership rates among credit-constrained households over recent decades, resulting in a rise in the aggregate homeownership rate that is comparable with the impact of population ageing. In countries where tax relief on mortgage debt financing is generous, however, the expansionary impact of mortgage market innovations on homeownership is smaller. This is consistent with the tendency for such housing tax relief to be capitalised into real house prices, which may crowd-out some financially constrained households from homeownership at the margin. The impact of housing policies regulating the functioning of the rental market, such as rent regulation and provisions for tenure security, on tenure choice is also explored. JEL classification: R21, R31, G21, H24. Keywords: Housing markets, homeownership, mortgage markets, financial regulation, taxation